Changes in sexual behaviour, following a diagnosis of HIV infection, in a group of South African males. - Baraldi, Ezio (My University, 2013)
Background: The inexorable spread of HIV infection across all continents is attributable to many factors, including male sexual behaviour. Such behaviour is often considered recalcitrant to change. Aim: The purpose of this study was to determine if sexual behaviour does or does not change after the diagnosis of HIV infection and to elucidate some of the psychosocial factors that may be operant in this context. Materials and Methods: The research consisted of a structured selfadministered questionnaire designed to measure ten psychosexual and sociosexual parameters in a group of HIV positive men. The questionnaire evaluated parameters at three different time points i.e. before HIV diagnosis, one year after HIV diagnosis and the present (2002). Participants were recruited from patients attending a private HIV treatment centre, in Pretoria, South Africa. Results: 53 participants completed the questionnaire. Descriptive statistics were used to elucidate trends. Statistically significant changes were seen in most studied domains, suggesting that beneficial change in sexual behaviour is possible after a diagnosis of HIV infection. These changes were seen, over time, in all the measured parameters, thus, change appears both possible and sustainable. This change was often detrimental to participants as it impacted negatively on some aspects of their personal and social functioning. Safer sex knowledge was weak in the studied group. Conclusion: The data indicate that change in behaviour is possible after a diagnosis of HIV infection and occurred in the studied population. Some changes were good for public health initiatives; many were detrimental to the psychosexual functioning of participants. Public health officials and other medical practitioners should include interventions aimed at reducing the negative psychosocial impact of HIV diagnosis at every patient encounter, as these changes do not resolve by themselves over time and are detrimental to the quality of life of patients.
Keywords: Sexual Behavior; HIV; Acquired Immunodeficiency Disease